Analysis of the distribution and molecular heterogeneity of the ospD gene among the Lyme disease spirochetes: evidence for lateral gene exchange. - Marconi, R T (1994)
Analysis of the ospD gene has revealed that this gene is not universal among Lyme disease spirochete isolates. The gene was found to be carried by 90, 50, and 24% of the Borrelia garinii, B. afzelii, and B. burgdorferi isolates tested. Size variability in the ospD-encoding plasmid was also observed. Sequence analysis has demonstrated the presence of various numbers of a 17-bp repeated sequence in the upstream control (promoter) region of the gene. In addition, a region within the coding sequence where various insertions, deletions, and direct repeats occur was identified. ospD gene sequences from 31 different isolates were determined and utilized in pairwise sequence comparisons and construction of a gene tree. These analyses suggest that the ospD gene was the target of several recombinational events and that the gene was recently acquired by Lyme disease spirochetes and laterally transferred between species.